Bone Marrow Transplantation in the Brazilian Northeast: Results of the first 100 transplants in Bahia State - Pallotta, Ronald; Cal, Flávia; Landeiro, Luciana; Espinheira, Ledivia; Dias, Thereza Christina Cruz; Santo, Thyago Espírito; Pinto, Tiago (Brazilian Journal of Transplantation, 2005)
Objective: This article presents the evolution of the first 100 transplanted patients in the Bone Marrow Transplantation Unit at Portuguese Hospital between February, 2000 and November, 2005. This unit is pioneer in the State of Bahia, Brazil, and one of the few transplant centers in the North and Northeast areas of the country. This is why this work is of major value. Methods: Forty-eight transplants were performed, being: myeloablative allogeneic, 5 non-myeloablative allogenic and 47 autologous. The mean age was 31 years, and most of them were male (59%). Diagnoses were: chronic myeloid leukemia (20), aplastic anemia (11), acute myeloid leukemia (07), myelodysplastic syndrome (06), acute lymphoblastic leukemia (04), non-Hodgkin lymphoma (12), Hodgkin disease (13), multiple myeloma (21), and autoimmune disease (06). Results: The overall 5 years survival rate was 52%, 60% for the autologous BMT, 47% for myeloablative allogeneic, and 40% for mini-allogeneic transplants. The mortality observed in the first 100 days was of 31%, 17% for autologous BMT, 46% for myeloablative allogeneic BMT, and 20% for mini-allogeneic. Conclusion: Data shows that even with all the difficulty attributed to social, economic and cultural peculiarities of that region, BMT is a feasible procedure, and the obtained results were satisfactory and similar found in other transplantation centers in the country and all over the world.